Anion influences on reactivity and NMR spectroscopic features of NHC precursors. Issue 61 (12th October 2018) - Huynh, Han Vinh; Lam, Truc Tien; Luong, Huyen T. T.
Abstract : The influences of 16 different counteranions on hydrogen-bondings, C–H acidities and 1 J C2–H coupling constants of azolium salts have been studied. Abstract : A series of 16 benzimidazolium salts of the type i Pr2 -bimyH + X − with various anions X were synthesized and characterized by various spectroscopic and spectrometric methods. Significant anion and solvent effects on the chemical shifts of the C2–H protons were found, which allows for a ranking of the anions in terms of their hydrogen-bond acceptor properties. Stronger acceptors could increase the acidity of their respective salts leading to a faster H/D exchange. Similar but less pronounced anion influences were detected for the 13 CC2 NMR resonances, while 1 J C2–H coupling constants appear to be anion and solvent independent.